Cultivation of Brazilian Spinach through Indoor Hydroponic System - Sulistyanto, Muhammad Prayadi; Agusulistyo, Ronny Dwi (International Journal of Applied Sciences and Smart Technologies, 2023)
Agriculture is a vital sector for a nation's livelihood. However, in the near future, the agricultural sector faces various challenges, particularly related to environmental and cultural issues. In this era of digital transformation, technology plays a crucial role in the agricultural field. Research is conducted to control the quality of nutrition and water intake for hydroponic plants to ensure their healthy and high-quality growth. The controlled parameters for nutrition include pH and nutrient solution availability, while water intake involves temperature, acidity (pH), electrical conductivity, and nutrient dosage. These parameters are detected by pH sensors, temperature sensors, EC (electric conductivity) sensors, and controlled by microcontrollers. The sensor detection results control the pump operation, ensuring a continuous and quality water intake rate. The growth of Brazilian spinach plants under study is observed with water pH controlled at 6.5 – 7 and nutrient electrical conductivity at 2 – 2.1 ms/cm.Test results demonstrate that the growth of plants in the research growth medium and the comparison growth medium significantly improves, even though the growth is not uniform across all plants. Plants in the research growth medium exhibit significantly better growth compared to those in the comparison growth medium.